Bacteriocin producing microbes with bactericidal activity against multidrug resistant pathogens - Leslie V.A; Khaloud Mohammed Alarjani; Arunkumar Malaisamy; Balamuralikrishnan Balasubramanian (Elsevier, 2021)
Background: Bacteriocins are proteins or peptides synthesized by bacteria that show inhibitory or killing activities against various bacteria. Bacteriocins are mainly considered for effective alternatives to different commercial antibiotics, preservatives in the food and pharmaceutical industries. Objectives: To screen and analyze novel bacteriocin-producing bacteria from the fermented food shidal for antibacterial activity against food pathogens and their molecular interactions studied through computationally. Methods: In this study, a strain Lactobacillus plantarum LA21 was isolated from the fermented food shidal identified based on morphological, biochemical, and 16S rDNA gene sequencing. The potent bacterium was subjected to improve bacteriocins production and characterized. Antimicrobial activity against drug-resistant bacteria and minimum inhibitory concentration (MIC) were determined. The bacteriocin was treated with proteolytic enzymes, and the mechanism of action on food pathogens was analyzed. Molecular docking studies were carried out as GLIDE module in the maestro tool of Schrodinger Software. Results: Bacteriocin was effective against pathogens such as Bacillus pumilus, Bacillus amyloliquefaciens, Staphylococcus aureus, and Listeria monocytogenes, with the most negligible MIC value was detected in L. monocytogenes. Furthermore, the depleted viability of bacterial cells indicated bacteriocin-induced cell lysis in L. monocytogenes via bactericidal activity. In addition, proteolytic enzyme digested bacteriocins revealed bacteriocin-like substances. Finally, molecular docking was performed to study the interactions between the targets and bacteriocins, results in relative intense contact with minimally 3 Å distance. Conclusions: The characteristic features of these bacteriocin-like molecules revealed that L. plantarum LA21 is a novel bacteriocin-producing bacterial strain to prepare novel antimicrobial drugs, feed additives or preservatives for future use in livestock and food industries.